Caracterización clínico-epidemiológica y estimación de riesgo cardiovascular de los pacientes atendidos en el CSN2 de Loja - Carpio Ordóñez, Evelin Solange (2021)
The continuous development of society, and changes in lifestyle have caused cardiovascular diseases to become the leading cause of death in the world, and in our country. For this reason, a descriptive, quantitative, retrospective cross-sectional investigation was developed, with the aim of clinically and epidemiologically characterizing the patients treated in the outpatient service of the Health Center N ° 2 of Loja according to their cardiovascular risk. 202 patients between 40 and 79 years of age were studied, where the risk was estimated through the use of the prediction tables of the WHO / ISH according to the epidemiological subregion (AMRD) for Ecuador, which predicts the risk of suffering fatal or non-fatal cardiovascular events in a period of 10 years, through variables such as sex, age, systolic blood pressure, total cholesterol, diabetes mellitus and tobacco consumption; obtaining the following results: low cardiovascular risk was present in 91.58% (n = 185), moderate in 7.43% (n = 15) and high in 0.99% (n = 2), no very high or higher risk patients were registered. The high risk was presented in both sexes equally, and its increase was directly proportional to age; regarding the epidemiological characteristics, the population comes from the urban area 99.01% (n = 200), basic educational level 56.44% (n = 114) and 40.10% (n = 81) are people who they do not work. The comorbidities found were obesity, followed by dyslipidemia and arterial hypertension. Keywords: cardiovascular diseases, myocardial ischemia.